Systemic and brain delivery of antidiabetic peptides through nasal administration using cell-penetrating peptides - Maeng, Jeehye; Lee, Kyunglim (Frontiers in Pharmacology, 2022)
The intranasal route has emerged as a promising strategy that can direct delivery of drugs into the systemic circulation because the high-vascularized nasal cavity, among other advantages, avoids the hepatic first-pass metabolism. The nose-to-brain pathway provides a non-invasive alternative to other routes for the delivery of macromolecular therapeutics. A great variety of methodologies has been developed to enhance the efficiency of transepithelial translocation of macromolecules. Among these, the use of cell-penetrating peptides (CPPs), short protein transduction domains (PTDs) that facilitate the intracellular transport of various bioactive molecules, has become an area of extensive research in the intranasal delivery of peptides and proteins either to systemic or to brain compartments. For the delivery of peptide antidiabetics, including insulin and exendin-4, for treating diabetes and Alzheimer’s disease. This review highlights the current status of CPP-driven intranasal delivery of peptide drugs and its potential applicability as a universal vehicle in the nasal drug delivery.